Indonesian EFL Students’ Writing Anxiety: Gender Overview - Hz, Benni Ichsanda Rahman (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study aims to examine the relationship between gender and foreign language writing anxiety among English as a Foreign Language (EFL) pre-service teachers’ students. Utilizing a qualitative case study, the research involved 56 participants, divided equally between male and female students, all enrolled in the English Language Education Study Program at a state university in North Sumatra. A survey of the Second Language Writing Anxiety Scale (SLWAS) was assigned to participants to determine their level of anxiety. To explore how gender, anxiety levels, and students’ experiences and engagement with second/foreign language writing anxiety are connected, the data gathered from the questionnaire were analyzed and grouped according to the participants’ gender. The data analysis shows show that among male respondents, 32.14% experienced high writing anxiety, 64.28% reported moderate anxiety, and 3.58% had low anxiety levels. For female respondents, 39.28% experienced high anxiety, 57.14% reported moderate anxiety, and 3.58% had low anxiety levels. Overall, both male and female participants possess varying levels of writing anxiety, with a higher percentage of females experiencing high anxiety compared to males, although the difference is not significant. More extensive research, incorporating a wider variable, is needed to deepen our understanding of how gender relates to writing anxiety.